Ultrathin Silicon Nanolayer Implanted NixSi/Ni Nanoparticles as Superlong‐Cycle Lithium‐Ion Anode Material. Issue 2 (20th November 2020) - Tamirat, Andebet Gedamu; Lui, Yao; Dong, Xiaoli; Wang, Congxiao; Wang, Yonggang; Xia, Yongyao
Abstract : It has been claimed that the mechanical properties of electrodes in lithium‐ion batteries have a huge impact on their electrochemical performance. This is especially critical for Si‐based electrodes, which suffer from pulverization and formation of an unstable solid–electrolyte interphase during cycling. Herein, thin silicon‐coated nickel silicide nanoparticles grown on a nickel inner core support (designated as Si@Ni x Si/Ni) as anode material for a Li‐ion battery are reported. The ultrathin nano silicon layer contributes to achieve reasonably high energy density and allows fast Li‐ion diffusion due to its high specific capacity and shortened Li‐ion diffusion length. While the gradiently distributed Nix Si layer enables the attainment of superior cycling stability and further enhances the specific capacity, the Ni inner core provides mechanical support to maintain the structural integrity of the nanoparticles during the extended lithiation/delithiation process. The Si@Ni x Si/Ni core–shell electrode exhibits a charge‐specific capacity of 706.1 mAh g −1 at a current density of 500 mA g −1 . This structure also shows a high first‐cycle Coulombic efficiency of 81.5%. Interestingly, the Si@Ni x Si/Ni core–shell electrode demonstrates a cycle life of over 5000 cycles with capacity retention of 74% at a current density of 500 mA g −1 . Abstract : Si@Ni x Si/Ni core–shell nanostructures are synthesized via facile one‐step ball milling from Ni and Si precursors. The Li‐ion battery with Si@Ni x Si/Ni core–shell anode material exhibits charge specific capacity of 706.1 mAh g −1 and excellent cycling performance of over 5000 cycles with capacity retention of 74% at a current density of 500 mA g −1 .